The Relationship Between Serum Levels of Total IgE, IL-18, IL-12, IFN- γ and Disease Severity in Children With Atopic Dermatitis (Mediators of Inflammation)
Studies about the role of cytokines on the immunopathogenesis of atopic dermatitis (AD) are generally based on in vitro observations and this role has not been completely clarified yet. Serum levels of total IgE, IL-18, IL-12, IFN- γ and the relationship between these parameters and disease severity, determined using the SCORAD index, in a group of atopic patients were investigated in this study. Serum levels of total IgE were measured by the nephelometric method and serum levels of IL-18, IL-12/p40 and IFN- γ were measured by ELISA method. Serum levels of total IgE and IL-18 were found significantly higher in study group than in controls ( p<.001 ) . There was no statistically significant difference between patients and controls in respect of serum levels of IL-12/p40 ( p=.227 ) . A statistically significant relationship between SCORAD values and serum levels of total IgE ( p<.001 ) , IL-18 ( p<.001 ) , and IL-12/p40 ( p<.001 ) was determined. These results show that serum levels of IL-18 can be a sensitive parameter that importantly correlates with clinical severity of AD, can play a role in the immunopathogenesis of AD, and furthermore may be used in the diagnosis and follow-up of the disease in addition to other parameters.